Cold plate performance enhancement based on parametric modeling of multiple structures - Zhao, Kai; Sun, Xiaoxia; Xia, Yuanqing; Li, Qiangqiang; Shen, Lili; Lin, Min (Frontiers in Energy Research, 2023)
Power electronic equipment to miniaturization, high integration direction while facing the problem of high heat flow density and uneven temperature distribution. The large temperature fluctuations and uneven temperature distribution in the operation of power electronic equipment will lead to thermal stress, and excessive thermal stress or uneven distribution will cause fatigue failure of the packaging material, resulting in reduced reliability, module failure, and reduced life of power electronic equipment. In this paper, we propose two kinds of liquid-cooled flow channel nonlinear reinforced heat transfer homogeneous liquid-cooled plate, which is theoretically derived to achieve the design requirement of uniform temperature on the heating side wall surface. The thermal design of the cold plate is carried out using ANSYS Workbench, and the indicators of various structures of the cold plate are analyzed and compared in terms of their ability to dissipate heat and maintain temperature uniformity. Based on the original runner structure, the heat dissipation performance of the rod structure and fin structure was evaluated, and the form of the internal heat dissipation structure of the runner was determined. The results show that the integrated liquid cooling plate temperature uniformity and flow resistance of both factors, the fin column heat sink is significantly better than the cylindrical fin column heat sink in the case of the same thermal resistance, the fin column heat sink flow resistance is significantly lower than the cylindrical fin column heat sink.